Empowering Students through Education and Training on the Production of Foot Sanitizer from Tea Leaf Waste - Riyanta, Aldi Budi; Purgiyanti, Purgiyanti; Amananti, Wilda (Journal of Community Service and Empowerment, 2026)
Tea leaf waste (TLW) is a household waste that can be processed into foot sanitizer to eliminate foot odor that is becoming increasingly popular. Applied products from the Pharmacy study program need to be disseminated to vocational school students as training products to enhance entrepreneurial knowledge and skills. SMK Al-Ikhlas Kota Tegal is Vocational High School one of the targets of the service activities because it aligns with the efforts to implement the School P5 program and the efforts to develop students' entrepreneurship. The aims of this service is to provide knowledge and improve skills in making foot sanitizer from tea waste for entrepreneurship skills. The activity method starts with a Focuss Group Discussion (FGD) to formulate the form of activities, followed by implementation in the form of education accompanied by direct training for students. The activity is concluded with an evaluation of the responses from the school and students in the form of pre-test, post-test, and questionnaire results of the activities. The results of this activity have been successfully carried out with the involvement of the twelfth-grade students of SMK Al-Ikhlas in educational and training activities. Evaluation of the pre-test and post-test also showed an increase in knowledge and skills. The activity was able to provide education and increase students' knowledge in processing TLW into foot sanitizer preparations in an effort to support P5 activities and SDGs efforts with an increased understanding of 48.73%. The evaluation of the activities was also assessed as very good with results reaching 94,4-100% response from students based on aspects of material, facilities, presenters, and participants' implementation responses, and it is hoped that similar activities will continue in the future.